Noribogaine reduces nicotine self-administration in rats - Chang, Qing; Hanania, Taleen; Mash, Deborah C; Maillet, Emeline L (Journal of psychopharmacology (Oxford), 2015)
Noribogaine, a polypharmacological drug with activities at opioid receptors, ionotropic nicotinic receptors, and serotonin reuptake transporters, has been investigated for treatment of substance abuse-related disorders. Smoking cessation has major benefits for both individuals and society, therefore the aim of this study was to evaluate the potential of noribogaine for use as a treatment for nicotine dependence. Adult male Sprague-Dawley rats were trained to self-administer nicotine intravenous. After initial food pellet training, followed by 26 sessions of nicotine self-administration training, the rats were administered noribogaine (12.5, 25 or 50 mg/kg orally), noribogaine vehicle, varenicline or saline using a within-subject design with a Latin square test schedule. Noribogaine dose-dependently decreased nicotine self-administration by up to 64% of saline-treated rats’ levels and was equi-effective to 1.7 mg/kg intraperitoneal varenicline. Noribogaine was less efficient at reducing food pellets self-administration than at nicotine self-administration, inhibiting the nondrug reinforcing effects of palatable pellets by 23% at the highest dose. These results suggest that noribogaine dose-dependently attenuates drug-taking behavior for nicotine, attenuates the reinforcing effects of nicotine and is comparable to varenicline power in that regard. The findings from the present study hold promise for a new therapy to aid smoking cessation.